ANALISIS RE-ENTRY SHOCK PADA MAHASISWA SELAMA TRANSISI DARI MODEL PEMBELAJARAN ONLINE KE PEMBELAJARAN TATAP MUKA DI MASA PANDEMI COVID-19 - Tumafto N. H. P. Mulyanto; Suryanto Suryanto; Wiwin Hendriani (Proyeksi: Jurnal Psikologi, 2023)
The Indonesian Ministry of Education, Culture, Research and Technology 2021 has implemented a hybrid learning model that allows students to return to face-to-face learning. This raises concerns about re-entry shock due to the transition to face-to-face learning. This research aims to study the re-entry shock experienced by students when returning to face-to-face learning model-based affection, behaviour, and cognition. This research uses a qualitative approach with an instrumental case study method. Data were obtained from questionnaires and interviews and analysed using theoretical thematic analysis. Findings showed that students experienced re-entry shock in all three aspects. However, the main problem came from the affective and cognition aspects, where students reported a need for more confidence in communicating, insecurity, and worries about the pandemic. Educators can use the results of this study better to understand the problems of re-entry shock in students and help them overcome them.